Osteoarthritis as an evolutionary legacy: Biological ageing and chondrocyte hypertrophy - Peter M. van der Kraan (Osteoarthritis and Cartilage Open)
Objective: Osteoarthritis (OA) is a progressive joint disease habitually linked to ageing, characterized by the gradual breakdown of cartilage leading to pain and reduced mobility. Historically viewed as mainly a “wear and tear” condition, new insights suggest that OA may be part of an evolutionary, age-related biological process rather than mainly driven by mechanical damage. Design: This conceptual paper discusses the model of antagonistic pleiotropy that proposes that certain genes beneficial early in life may contribute to diseases in the context of OA. Results: Findings indicate that OA is connected to biological and not to chronological age supporting the idea that OA is not merely a wear and tear process. Chondrocyte hypertrophy, essential in endochondral bone formation at a (pre)reproductive age, is stimulated by a displaced and wrongly timed endochondral ossification quasi-program in age-related OA. Age-related chondrocyte hypertrophic differentiation in articular cartilage is likely driven by loss of loading-induced TGF-β signaling. Conclusion: Comprehending OA within this evolutionary and biological frame provides a solid alternative to the theory of “wear and tear”, offering insights into further understanding, prevention and disease management.